TRANSFORMING LEGAL PROCEEDINGS IN INDONESIA’S ADMINISTRATIVE COURT: THE ROLE OF LEGAL CULTURE IN THE SOCIETY 5.0 ERA - Lumbanraja, Brata Yoga; Utama, Yos Johan; Putrijanti, Aju; Garunja, Evis (Faculty of Law, Universitas Diponegoro, 2025)
This study explores the integration of technology in Indonesia’s Administrative Court system, particularly the impact of electronic justice (e-court) in the Society 5.0 era. With advancements in technology reshaping societal functions, the study examines how these changes have influenced legal proceedings within the Administrative Court. The research focuses on the implementation of Supreme Court Regulation No. 1 of 2019, which governs e-court proceedings, and how these technological advancements align with Indonesia’s legal culture and the values of Pancasila, particularly social justice. It highlights fundamental shifts, such as the introduction of electronic summons, electronic domicile, and online hearings, as part of the modernization of judicial processes. Through qualitative research and doctrinal legal analysis, this study emphasizes the significance of legal culture in ensuring the smooth transition to digital procedures and fostering public awareness of citizens’ rights and obligations. The findings suggest that while technological progress in the court system brings efficiency, the successful adoption of these changes requires legal culture to promote public understanding and participation, ultimately supporting the realization of social justice as outlined by Pancasila.